Determination of pyrethroids in water samples by dispersive solid‐phase extraction coupled with high‐performance liquid chromatography. (28th November 2022) - Zhang, Jie; Wang, Ya; Yu, Jun; Wang, Qingying; Khattak, Kashif Nawaz; Yang, Xiupei
Abstract: A metal–organic framework UiO‐66 was prepared and used as a sorbent for dispersive solid‐phase extraction combined with high‐performance liquid chromatography (DSPE‐HPLC) for extracting and determining four pyrethroids in water samples for the first time. The as‐synthesized material was confirmed by Fourier transform infrared spectroscopy (FT‐IR), transmission electron microscopy (TEM), scanning electron microscopy (SEM), X‐ray diffraction (XRD), thermogravimetric analysis (TGA), and N2 adsorption–desorption analysis. In addition, several important parameters affecting DSPE efficiency, including sorbent dosage, extraction time, salt concentration, pH, elution solvent, elution volume, and elution time, were optimized. Under the optimum conditions, the UiO‐66 based on the DSPE‐HPLC method displayed a wide linear range (10–1000 ng/ml), low limits of detection (2.8–3.5 ng/ml), and good precision (relative standard deviations [RSDs] < 3%) for the four pyrethroids. The recoveries at different spiked levels ranged from 89.3% to 107.7%. In addition, UiO‐66 featured good reusability and reproducibility. The results demonstrated that π–π stacking interactions, hydrophobic interactions, and van der Waals forces between UiO‐66 and the four pyrethroids played a crucial role in the adsorption process. Meanwhile, the maximum extraction capability could be obtained within 5 min. Thus, the DSPE coupled with the UiO‐66 sorbent can be successfully used in the analysis of four pyrethroids in environmental water samples. Practitioner Points: Simultaneous determination of four pyrethroids using the developed UiO‐66‐based DSPE‐HPLC method in water samples. The developed method had a short enrichment time, broad linear ranges, a low detection limit, and high enrichment factor. It is showed that π–π stacking interaction, hydrophobic interaction, and van der Waals forces were the main mechanism. Abstract : A method for simultaneous determination of four pyrethroid pesticide residues in water samples was developed by dispersive solid‐phase extraction with UiO‐66 sorbent coupled with high‐performance liquid chromatography.